2022
DOI: 10.1002/eqe.3691
|View full text |Cite
|
Sign up to set email alerts
|

Uniform risk spectra for rocking structures

Abstract: This paper presents uniform risk spectra for zero stiffness bilinear elastic (ZSBE) systems. The ZSBE oscillator is a bilinear elastic system with zero post‐“yield” stiffness that satisfactorily predicts the response of different systems with negative lateral stiffness (e.g., free‐standing or restrained rocking blocks). It can be described by a single parameter; thus, it is simpler to produce its spectrum. Using the ZSBE proxy, this paper provides the uniform risk spectra for sites in six locations in Europe. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…PGV was used as an intensity measure, as it performs better than PGA or PGD for rocking structures. [104][105][106][107][108][109][110][111] Figures 10,11,and 12 show the median rocking spectra for the far-field, near-field pulse-like, and near-field no pulse-like record bins, derived for different processing schemes. As stated earlier, all the rocking spectra in this paper are derived for size (2H) of 2000 m, which represent the case when 2H→∞ that is being studied for mathematical completeness.…”
Section: Rocking Spectra Resultsmentioning
confidence: 99%
“…PGV was used as an intensity measure, as it performs better than PGA or PGD for rocking structures. [104][105][106][107][108][109][110][111] Figures 10,11,and 12 show the median rocking spectra for the far-field, near-field pulse-like, and near-field no pulse-like record bins, derived for different processing schemes. As stated earlier, all the rocking spectra in this paper are derived for size (2H) of 2000 m, which represent the case when 2H→∞ that is being studied for mathematical completeness.…”
Section: Rocking Spectra Resultsmentioning
confidence: 99%
“…For an ensemble of ground motions to be useful, in this paper all ground motions were scaled to the same PGV. PGV was used as an intensity measure, as it performs better than PGA or PGD for rocking structures [43,44].…”
Section: Resultsmentioning
confidence: 99%
“…However, the aim of this work is not to describe the response of the rocking oscillator in function of the six parameters of the Rezaeian and Der Kiureghian model, but in function of well‐known IMs. Numerous ground motion IMs (and combinations of IMs) [ 66–78 ] have been suggested for the rocking block. The present study concentrates on few, well‐established IMs, which are relatively easy to compute.…”
Section: Description Of the Analysismentioning
confidence: 99%
“…Studying free and restrained rocking systems of negative systems under sets of far‐field, near‐field pulse‐like and near‐field non‐pulse‐like ground motions, Manzo et al. [ 75–77 ] concluded that PGV performs overall better than PGA. Vassiliou and Sieber [ 78 ] studied 3D rocking and concluded that the displacement response scales with a bivariate intensity measure that includes both PGA and PGV.…”
Section: Introductionmentioning
confidence: 99%